2011
DOI: 10.1002/asia.201100347
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Anthraquinone–Resin Hybrid Co‐Catalyst for Fenton‐Like Reactions: Acceleration of the Iron Cycle Using a Quinone Cycle under Visible‐Light Irradiation

Abstract: The Fenton reaction (H 2 O 2 +Fe 2 + /Fe 3 + ) has been widely used to oxidize organic compounds for various purposes, such as DNA damage by free radicals, [1] organic or inorganic synthesis, [2] and environmental detoxication. [3] As a versatile catalysis system, Fenton-like reactions have particular features: readily available and inexpensive reagents, extremely large rate constants (ca. 10 9 m À1 s À1 ), and a facile procedure. [4] The generally accepted free-radical-chain mechanism for the Fenton reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The presence of persistent organic pollutants, such as industrial dyes, antibiotics, and hexavalent chromium Cr­(VI), in the wastewater has caused great concern because of their incomplete elimination and persistent pollution of the environment. Because of the large volume of industrial and municipal wastewater, advanced water treatment techniques are essential for maintaining healthy water circulation. Advanced water treatment techniques for organic pollutant degradation rely on the Fenton reaction (Fe 2+ /H 2 O 2 ) to generate • OH. Nevertheless, in a traditional Fenton reaction system, the free ferrous ions can be quickly expended, and this process requires the addition of Fe 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of persistent organic pollutants, such as industrial dyes, antibiotics, and hexavalent chromium Cr­(VI), in the wastewater has caused great concern because of their incomplete elimination and persistent pollution of the environment. Because of the large volume of industrial and municipal wastewater, advanced water treatment techniques are essential for maintaining healthy water circulation. Advanced water treatment techniques for organic pollutant degradation rely on the Fenton reaction (Fe 2+ /H 2 O 2 ) to generate • OH. Nevertheless, in a traditional Fenton reaction system, the free ferrous ions can be quickly expended, and this process requires the addition of Fe 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47][48][49][50] However, it should be pointed out that the heterogeneous Fenton reaction itself is too slow, especially those containing Fe III oxides, due to the slow reduction of Fe III to Fe II (k = 0.001-0.1 m À1 S À1 ). [51][52] Therefore, most heterogeneous Fenton catalysts are used in an aqueous environment with the assistance of UV irradiation for the acceleration of the reaction, resulting in the need for specific equipment at additional cost. In this respect, it is well-understood that significant attention has been directed towards using solar-driven heterogeneous Fenton catalysts with a high catalytic activity and long-term stability.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, in a large number of studies in the past few decades, these heterogeneous catalysts have demonstrated their usefulness in treating various organic pollutants in an aqueous environment 4550. However, it should be pointed out that the heterogeneous Fenton reaction itself is too slow, especially those containing Fe III oxides, due to the slow reduction of Fe III to Fe II ( k =0.001–0.1 M −1 S −1 ) 5152. Therefore, most heterogeneous Fenton catalysts are used in an aqueous environment with the assistance of UV irradiation for the acceleration of the reaction, resulting in the need for specific equipment at additional cost.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these drawbacks, heterogeneous Fenton‐like reaction has become an alternative technology, in which H 2 O 2 is converted to ⋅OH on solid catalyst surface. Among various catalysts, magnetic nanoparticles (NPs) are deeply studied owing to extensive source, high efficiency and magnetic separation ,. Unfortunately, magnetic NPs easily aggregate because of high surface energy and strong anisotropic dipolar interactions, which reduces their catalytic activity.…”
Section: Introductionmentioning
confidence: 99%